A new method for processing ultrasonic gas flowmeter signal in wet gas. Issue 1 (10th December 2020) - Wang, Mi; Zheng, Dandan; Mei, Jianqiang; Mao, Yang; Hu, Jiayu
Abstract: Gas velocity as an important characteristic parameter of wet gas has become a very active research issue in engineering field. Among many gas velocity measurement techniques, the ultrasonic flowmeter technique is more suitable for actual working conditions. However, the traditional signal processing methods of ultrasonic flowmeter are only proposed for single‐phase gas. In wet gas, the ultrasonic signals fluctuate greatly, are easily distorted and even lost, so the single‐phase ultrasonic signal processing methods are not applicable. Therefore, a new ultrasonic signal DBSCAN clustering synthetic peak method is proposed to solve the above problems. To verify the feasibility of this new proposed method, three real flow experiments are carried out on horizontal pipe at ambient temperature and pressure. Additionally, comparing the gas velocity results using ultrasonic signal double threshold method and ultrasonic empirical model method for single‐phase gas and the new proposed method for wet gas, it is shown that the measurement results using new proposed method accord with the theoretical law and can accurately measure the gas velocity. Furthermore, the three real flow experimental results show that the repeatability of gas velocity in wet gas by the new proposed method is mostly <0.5%.